1996
DOI: 10.1152/jappl.1996.81.1.172
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic tissue changes in rats flown on Spacelab Life Sciences-2

Abstract: Thymus, spleen, inguinal lymph node, and bone marrow specimens from rats flown on the 14-day Spacelab Life Sciences-2 mission were examined after staining of tissue sections. The primary observation was a transient retrogressive change in lymphatic tissues in the rats within a few hours after landing. There was a diffuse increase in tingible body-containing macrophages in the cortex of the thymus, thymus-dependent areas of the splenic white pulp, and inguinal lymph node. This was not observed 9 days after reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 0 publications
3
26
0
Order By: Relevance
“…The results in regard to thymus mass are more variable because thymus mass has been reported to decrease16, increase18 or remain unchanged compared to controls192021. Observed reductions in spleen and thymus mass are often explained by a stress response2223.…”
Section: Discussionmentioning
confidence: 99%
“…The results in regard to thymus mass are more variable because thymus mass has been reported to decrease16, increase18 or remain unchanged compared to controls192021. Observed reductions in spleen and thymus mass are often explained by a stress response2223.…”
Section: Discussionmentioning
confidence: 99%
“…IL-2 production decreased after space flight for three different T cell subsets (CD3 + , CD4 + and CD8 + ) and IFN-production decreased in the CD4 + subset (Crucian et al, 2000). Spaceflight studies performed with rodents have found that microgravity caused rodents to be more susceptible to infection (Sonnenfeld et al, 1988), inhibited NK cell activity (Rykova et al, 1992), reduced capability for wound healing (Davidson et al, 1999), inhibited INF-production (Gould et al, 1987) and a reduction in lymphoid organ size (Congdon et al, 1996). A study using rhesus monkeys, microgravity inhibited IL-1 production and decreased response to colony stimulating factor (CSF) on bone marrow cells (Sonnenfeld et al, 1996).…”
Section: Microarray Analysis Of Microgravity Exposed Cells Of the Immmentioning
confidence: 99%
“…Some findings of studies performed with rodents include loss of resistance to infection (Sonnenfeld et al, 1988), inhibited NK cell activity (Rykova et al, 1992), reduced capability for wound healing (Davidson et al, 1999), inhibited INF-gamma while IL-3 production remained unchanged (Gould et al, 1987) and a reduction in lymphoid organ size (Congdon et al, 1996). A study performed on pregnant rats showed that while the parents' immune responses were affected by the conditions of space flight, their offspring showed no alteration to normal ground values .…”
Section: Cell-mediated Responses; T-cell and B-cell Functionality Andmentioning
confidence: 99%